Impact of Postacute Care on Depression and Anxiety in Patients with Stroke: Cognitive Function as a Mediator and Moderator - Shi-Jer Lou; Hsiu-Fen Lin; Chau-Chyun Sheu; Hong-Yi Hsu; Hon-Yi Shi (Asian Journal of Social Health and Behavior)
Introduction: This study explored whether cognitive function mediates the impact of postacute care (PAC) programs on depression or anxiety in patients with stroke, with consideration for potential moderation effects in the pathway. Methods: A PAC group (n = 2087) receiving PAC for stroke was compared to a non-PAC group (n = 1591) receiving standard stroke care in Taiwan from March 2015 to March 2023. The effects of PAC on cognitive function and depression and anxiety at baseline, 12th week, and 1st year after rehabilitation were investigated using Hayes’ Models. The model was estimated via maximum likelihood with robust standard errors and significance of indirect effects were assessed via a Sobel test. The effect of each variable on the moderation of different pathways in the model was analyzed using AMOS 23.0, and The SPSS PROCESS macro also was used to perform the mediation analysis. Results: The PAC program had a mediating effect on cognition and depression at week 12 (a × b = −0.098, P < 0.001) on cognition and anxiety at week 12 (a × b = −0.107, P < 0.001), and the PAC program had a direct effect on depression and anxiety in the 1st year. It was found that acute lengths of stay had a significant moderation effect in the model (X × W → M = 0.204, P = 0.002), but the model lost its mediating effect when the m oderation variable was added. Conclusion: Patients with stroke should receive PAC as soon as possible to improve their cognitive function after rehabilitation, to maximize the effectiveness of treatment for mental disorders, and to reduce the burden of the disease.